Normal bowel habites in a sample of healthy Iraqi population - Taqa, Layth Rafea; Shubbar, bAmira H.; Haji, Ghazi F. (AL-Kindy College Medical Journal, 2014)
Background: Clinicians and investigators consider the normal range of bowel habit and frequency as between 3 to 21 motions per week . Stool frequency out side the normal range may be unusual but may not be abnormal in the sense of a disease . And according to the consistency, the normal stool ranges from porridge like to hard and pellety .Objectives: To establish a basic data about the bowel habits (consistency and frequency) in a sample of healthy Iraqi population; in addition to learn about their definition of constipation and diarrhea.Methods: Prospective study from Jan 2000- Jun 2000 at Al-Yarmouk teaching hospital, Baghdad. Questionnaires were distributed to 950 healthy persons of different age group .The questionnaire included: Detailed history of bowel habit with definitions of constipation and diarrheaResults: Five hundred and eighty eight (588) person responded to the questionnaire:Five hundred and twenty three (523) (94.6.6%) of the respondents had a normal frequency 3-21/week. Four hundred and sixty nine (469) (84.4%) have a doughy (normal) consistency. Most of the respondents who have less frequent stool were females (5.9%), comparable to the predominant male gender in the frequent loose stool group (2%).More than seven percent (7.7%) of the respondents had bleeding per rectum once or more in their life, less than half of them sought the advice of the doctor. Increased “liquidity” was the main definition of diarrhea while “straining” was the main definition of constipation.Conclusions:. This study showed that, most of the studied populations have a rather normal frequency and consistency of stool. Those subjects with less frequent and pellet stool were mainly female compared to more frequent motion number in male gender and frequent increase in the liquidity. Blood was not always an alarming feature to seek for medical advice